2014
DOI: 10.3892/ijo.2014.2278
|View full text |Cite
|
Sign up to set email alerts
|

Nestin regulates proliferation, migration, invasion and stemness of lung adenocarcinoma

Abstract: Lung cancer is the most common cancer and the most common cause of cancer-related death in the world. Nestin, a class VI intermediate filament, is known to be a cancer stem cell (CSC) marker as well as a neuroepithelial stem cell marker. High expression levels of nestin are reported in several types of cancers including lung, pancreatic and prostate cancers. Nestin is thought to regulate tumor cell proliferation, migration, invasion and CSC properties. Here, we confirmed nestin expression in non-small cell lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 54 publications
3
70
0
Order By: Relevance
“…Our previous studies have shown that nestin regulates the sphere formation ability of glioblastomas, melanomas, lung adenocarcinomas, and pancreatic cancer [23][24][25]. In this study, nestin was detected in perivascular and perinecrostic lesions, which are considered a niche for BTSCs.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Our previous studies have shown that nestin regulates the sphere formation ability of glioblastomas, melanomas, lung adenocarcinomas, and pancreatic cancer [23][24][25]. In this study, nestin was detected in perivascular and perinecrostic lesions, which are considered a niche for BTSCs.…”
Section: Discussionmentioning
confidence: 49%
“…We have also shown that knockdown of nestin expression suppresses migration, invasion, and sphere formation in pancreatic cancer [22,23], malignant melanomas [24] and lung cancer [25]. Similarly, Lu et al demonstrated that blocking the expression of nestin in glioblastomas by intratumoral injection of shRNA significantly reduced tumor growth and volume [19].…”
Section: Introductionmentioning
confidence: 93%
“…Nestin expression in tumour samples positively correlated with tumour size, lymph node metastasis and there was negative association with survival. On cell lines, it corresponded with increased proliferation, migration and invasion capacities [25]. Basing on our results and presented studies, nestin detection may serve in the future, as a biomarker used to predict prognosis and facilitate patient-oriented approach to treatment.…”
Section: Discussionmentioning
confidence: 95%
“…When it comes to nestin and other lung malignancies, it was identified as CSC marker in non-small cell lung cancer (NSCLC) [24]. Narita et al found nestin on immunohistochemical analysis performed on surgical specimens of NSCLC [25].…”
Section: Discussionmentioning
confidence: 99%
“…The acceleration of cancer cell proliferation, invasive growth and migration have previously been reported to correlate with nestin expression in several cancer types (22)(23)(24). These features are cellular mechanisms underlying cancer progression and metastasis, and they are also common characteristics found in ATC cells.…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 92%